Is multileaf collimator tracking or gating a better intrafraction motion adaptation strategy? An analysis of the TROG 15.01 stereotactic prostate ablative radiotherapy with KIM (SPARK) trial. (October 2020) - Hewson, Emily A; Nguyen, Doan T; O'Brien, Ricky; Poulsen, Per R; Booth, Jeremy T; Greer, Peter; Eade, Thomas; Kneebone, Andrew; Hruby, George; Moodie, Trevor; Hayden, Amy J; Turner, Sandra L; et al.
Highlights: Prostate motion during SABR can result in inaccurate radiation dose delivery. Both MLC tracking and gating were effective methods for real-time motion adaptation. MLC tracking and gating were comparable dosimetrically. Gating resulted in more interruptions to the clinical workflow. Abstract: Purpose: Stereotactic Ablative Radiotherapy (SABR) has recently emerged as a favourable treatment option for prostate cancer patients. With higher doses delivered over fewer fractions, motion adaptation is a requirement for accurate delivery of SABR. This study compared the efficacy of multileaf collimator (MLC) tracking vs. gating as a real-time motion adaptation strategy for prostate SABR patients enrolled in a clinical trial. Methods: Forty-four prostate cancer patients treated over five fractions in the TROG 15.01 SPARK trial were analysed in this study. Forty-nine fractions were treated using MLC tracking and 166 fractions were treated using beam gating and couch shifts. A time-resolved motion-encoded dose reconstruction method was used to evaluate the dose delivered using each motion adaptation strategy and compared to an estimation of what would have been delivered with no motion adaptation strategy implemented. Results: MLC tracking and gating both delivered doses closer to the plan compared to when no motion adaptation strategy was used. Differences between MLC tracking and gating were small with differences in the mean discrepancy from the plan of −0.3% (CTV D98% ), 1.4% (CTV D2% ), 0.4% (PTV D95% ), 0.2% (rectum V30Gy ) and 0.0% (bladder V30Gy ). On average, 0.5 couch shifts were required per gated fractions with a mean interruption duration of 1.8 ± 2.6 min per fraction treated using gating. Conclusion: Both MLC tracking and gating were effective strategies at improving the accuracy of the dose delivered to the target and organs at risk. While dosimetric performance was comparable, gating resulted in interruptions to treatment. Clinical trial registration number: NCT02397317.